Validation of the Career-Related Parent Support Scale among Portuguese students - Gamboa, Vitor (2021)
The Career Related Parent Support Scale (CRPSS), in accordance with the main sources of self-efficacy, assesses the perceived parental support according to four dimensions: career modeling, emotional support, instrumental support, and verbal persuasion. The aim of the present study was to analyze the psychometric properties of a Portuguese version of the CRPSS in a sample of 338 students from basic and secondary education. Overall, the analyzes performed on the items and on the different subscales attest to the psychometric quality of the CRPSS. A confirmatory factor analysis revealed that the adjustment to the four-factor model was satisfactory, although it was necessary to eliminate three items, which seems to be in line with the results found in other validation studies. The CRPSS was significantly associated with self-efficacy in decision making and career exploration behaviors, showing its convergent validity. These findings seem to support the use of the Portuguese version in the evaluation of perceived parental support among Portuguese adolescents.